Synthesis, Crystal Structure of Poly-catena-[(1-ethyl-3-isopropyl-imidozolium)hexa-iodo-tetra silver(I)] - Guo Wang, Zhi; Guo, Ying; Hui Liao, An; Mei Zhang, Han (Asian Journal of Chemistry, 2014)
The complex [(CH3)2CH{CH(NCHCHN)CH2CH3}+]2n[(Ag4I6)2-]n has been synthesized by the reaction of Ag2O with [(CH3)2CH{CH(NCHCHN)CH2CH3}]+ I- in a 1:3 molar ratio at 173 °C in DMSO and characterized by elemental analysis, 1H NMR and single-crystal X-ray diffraction analysis. It crystallizes in orthorhobic, space group Pca21 with a = 21.315(9), b = 7.202(3), c = 21.380(10)Å, b = 90° V = 3282(2) Å3, Mr = 1471.32, Z = 4, Dc = 2.978 g/cm³, μ(MoKa) = 8.01 mm-1 and F(000) = 2640. The structure was refined to R = 0.0303 and wR = 0.061 for 2758 observed reflections with I > 2s(I). The asymmetric unit of the title complex [(CH3)2CH-{CH(NCHCHN)CH2CH3}+]2n[(Ag4I6)2-]n is a ionic coordination polymer, consisting of two substituted imidazolium cation and an infinite anionic [Ag4I6]2- chain. Within the chain the Ag(I) ions have distorted tetrahedral geometry when the Ag-Ag interactions are not taken into account, which are coordinated by four iodide ions. Meanwhile the iodide ions link four neighboring Ag atoms, whereas iodide acts as a bridge between two Ag atoms. A four-membered ring system is formed by corner sharing of the AgBr4 tetrahedra.